2007
DOI: 10.1152/ajplung.00430.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 mediates TGF-β1-induced retinoblastoma protein phosphorylation, proliferation, and hypertrophy in human airway smooth muscle cells

Abstract: TP. Nox4 mediates TGF-␤1-induced retinoblastoma protein phosphorylation, proliferation, and hypertrophy in human airway smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 71 publications
(93 reference statements)
6
96
0
1
Order By: Relevance
“…The former include plateletderived growth factor (PDGF), epidermal growth factor (EGF), and TGF-b (42-45), whereas the latter include histamine, thrombin, endothelin, and tryptase (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). EGF and TGF-b are synthesized by airway epithelial cells (57,58), consistent with the notion that epithelial damage induces production of paracrine growth factors, which stimulate airway smooth muscle growth (Figure 2).…”
Section: Biochemical Mechanisms Of Airway Smooth Muscle Proliferationmentioning
confidence: 57%
“…The former include plateletderived growth factor (PDGF), epidermal growth factor (EGF), and TGF-b (42-45), whereas the latter include histamine, thrombin, endothelin, and tryptase (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). EGF and TGF-b are synthesized by airway epithelial cells (57,58), consistent with the notion that epithelial damage induces production of paracrine growth factors, which stimulate airway smooth muscle growth (Figure 2).…”
Section: Biochemical Mechanisms Of Airway Smooth Muscle Proliferationmentioning
confidence: 57%
“…Studies show that preventing TGF-b1 overexpression or signaling reduces and/or leads to a parallel decline in HASM hypertrophy (89). It is suggested that TGF-b1 may mediate its effects on HASM hypertrophy through the activation of NOX4 (81).…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 99%
“…For example, NOX4-mediated ROS production in human pulmonary artery smooth muscle cells in response to TGF-β occurs primarily intracellularly, and NOX4 appears to localize to the ER or the nucleus (186). Accordingly, NOX4 activation was associated with intracellular ERK1/2 signaling and phosphorylation of nuclear or ER proteins, such as retinoblastoma protein and eukaryotic translation initiation factor 4E binding protein-1, thereby mediating smooth muscle cell proliferation and hypertrophy (186,193). In contrast, myofibroblasts obtained from patients with iodopathic pulmonary fibrosis were found to produce primarily extracellular H 2 O 2 in response to TGF-β1, and are thereby capable of inducing cell death in neighboring pulmonary epithelial cells, suggesting the association of NOX4 with the plasma membrane as a paracrine signaling molecule (187).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…Observations of NOX4 induction by TGF-β in pulmonary fibroblasts or smooth muscle cells strongly suggest its importance in pulmonary fibrosis or airway remodeling during chronic lung diseases such as asthma (187,193). Indeed, recent analysis of lung tissues from patients with pulmonary arterial hypertension revealed ã 2.5-fold upregulation of NOX4, which is believed to contribute to oxidant-mediated smooth muscle cell proliferation (81).…”
Section: Other Nox'smentioning
confidence: 99%